EFEKTIVITAS LATIHAN INTERVAL TRAINING DALAM MENINGKATKAN VO2MAX PEMAIN SEPAKBOLA - Angga Apriana Angga (Journal of Physical Education and Sport Science, 2022)
This study aims to determine the effectiveness of Interval Training in increasing Vo2Max of Football Players of Club Persiba Baok FC. This study uses an experimental method with the design of One Group Pretest – Posttest Design. The population in this study was the 25 athletes of Club Persiba Baok FC Football Players. The sampling technique used is total sampling where the number of samples is the same as the population. The instrument used is the MFT (Multistage Fitness Test) Bleep Test which has been determined from (State Ministry of Youth and Sports of the Republic of Indonesia, 2005). The results of the study were carried out by analyzing the initial test data(pretest) with the results for the interval training method using the bleep test method with an average (mean) of 33.20 and a standard deviation of 1.280. After doing the treatment and analysis of the final data (posttest) the results for the interval training method using the bleep test method with an average of 51.44 and a standard deviation of 0.822. Which means that the final test results show that the interval training method can increase the Vo2max of soccer players.